ANALISIS KINERJA REKSADANA SYARIAH DI INDONESIA PERIODE 2014-2016 - Yuhasril Yuhasril (Jurnal Ilmiah Manajemen dan Bisnis, 2018)
This study aims to determine the performance of Islamic Mutual Funds in Indonesia in the period 2014 – 2016 and to know the type of Islamic Mutual Funds that have outperformance. Sample in this study as many as 23 mutual funds sharia in Indonesia are registered in the Financial Services Authority. The research design used is descriptive quantitative and Nett Asset Value data is processed by Sharpe Ratio, Treynor Ratio and Jensen Ratio. The results are 17 islamic mutual funds have a good performance, while 6 islamic mutual funds have a underperformance. The type of Islamic Mutual Fund that have outperformance is Protected. The second choice is Mixed or Stock which is can be used as alternative investment.